Parsimonious Analogical Reasoning for Smart Decision Support in Network-enabled Environments: Managing Situational Awareness - Louvieris, Panos; Gregoriades, Andreas; Mashanovich, Natasha; White, Gareth (My University, 2006)
How information is managed and exploited to support commanders’ intuitive decision making during the execution of a plan is a key consideration in the development of a true networked enabled capability (NEC). While the benefits of NEC are laudable i.e. better networks, better information sharing and situational awareness, better decisions, better actions and better effects, commanders and their staff are nevertheless faced with an overwhelming amount of data; in practice, this can often lead to inconsistent perspectives and tempo stagnation impeding decision and operational effectiveness. Therefore reducing the information volume requirement and servicing commanders’ critical information requirements (CCIRs) through parsimonious information fusion is fundamental to maintaining situational awareness (SA) in the battlespace and achieving decision effectiveness. This paper outlines and demonstrates an analogical reasoning approach for smart decision support in NEC which employs soft Case Based Reasoning (CBR) techniques incorporating Critical Success Factors (CSFs). The effectiveness of this approach is illustrated using a war-gaming case study implemented on a Computer Generated Forces (CGF) test-bed.
Keywords: Cognitive Domain Issues; C2 Modelling and Simulation; Network Centric Metrics